Vegan Camembert, a sustainable alternative with resistance to mycotoxin formation comparable to that of conventional milk-based Camembert - Nicole Ollinger; Lisa Schütz-Kapl; Alexandra Schamann; Alexandra Malachova; Michael Sulyok; Markus Gorfer; Annabella Wohletz; Franciso Cerqueira; Harald Berger; Bernhard Blank-Landeshammer; Angeline Rochard; Rudolf Krska; et al. (Future Foods)
Plant-based and sustainable lifestyles are becoming increasingly popular. There are many reasons for this, including to mitigate animal suffering, to protect the environment or because it is healthier than an animal-based diet. The risk of mycotoxin ingestion from increased consumption of fermented nuts and other raw materials used in vegan Camembert alternatives, which may be susceptible to mycotoxin formation, is poorly understood. Therefore, the mycotoxin concentrations of purchased conventional Camembert and vegan alternatives were analyzed and compared. To monitor potential mycotoxin formation during ripening, homemade Camembert prepared with conventional milk, lactose-free milk and a vegan alternative made from poppy seeds and hazelnuts were evaluated by targeted metabolite profiling. Poppy seeds and hazelnuts were chosen as regional raw materials, known as a sustainable replacement for cashew or palm oil products. None of the tested products contained mycotoxins sensu stricto. Mycotoxins such as cyclopiazonic acid from Penicillium camemberti were detected only on special agar plates.